Pengaruh Kualitas Pelayanan dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Pada Jasmine Salon Beauty Dan SPA Kabupaten Toraja Utara - Meryani Borong; Althon K. Pongtuluran; Astriwati Biringkanae (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
The Influence of Service Quality and Customer Loyalty at Jasmine Beauty Salons and Spa North Toraja District". The purpose of this study was to find out whether there is an influence of service quality and customer satisfaction on customer loyalty in the Jasmine Beauty Salons and Spa in Tallunglipu Sub-Dstrict, North Toraja District . Data collection procedures from this study are: observation, questionnaires, and documentation. The data analysis technique is quantitative with multiple linear regression tests. The results of calculations with the F test obtained the results of F count 43,165 with F table 3.090. Based on the results of calculations with the T test on the cooperative image variable, the result is T count (2,734) < T table (1.986) and on the service quality variable, the result is T count (4,458) > T table (1.986). The conclusion of this study is that the service quality variable has no effect on loyalty customer at the Jasmine Beauty Salons and Spa North Toraja District and the customer satisfaction variable has an effect on loyalty customer at the Jasmine Beauty Salons and Spa North Toraja District.